Warriors. Skyclan & the stranger. beyond the code / #2 - Jolley, Dan.; Hunter, Erin.; Barry, James L., 1979- (New York : Harper, 2011)
Sol has joined SkyClan's ranks and, unbeknownst to Leafstar, may be leading her Clanmates astray, so Leafstar must determine whether or not to trust the stranger in her ranks--at the risk of jeopardizing SkyClan's future.
Keywords: Cats -- Fiction; Fantasy; Graphic novels; Graphic novels